2011
DOI: 10.1016/j.ejcts.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Results of mechanical circulatory support in France

Abstract: MCS is an essential therapeutic tool to save the life of young patients with cardiogenic shock or advanced cardiac failure. Early MCS implantation and the availability of a device that is adapted to the patient's clinical status are prerequisites for reducing overall mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…However, our finding corroborates that of the national French GRAM registry (Groupe de R eflexion sur l'Assistance M ecanique), which showed that among 520 mechanical circulatory support recipients implanted in France between 2000 and 2006, 73% underwent biventricular support [7]. One potential explanation is that many recipients were referred too late, once the patient was in severe cardiogenic shock with multiorgan dysfunction, thus precluding safe isolated left ventricular support.…”
Section: Commentsupporting
confidence: 89%
“…However, our finding corroborates that of the national French GRAM registry (Groupe de R eflexion sur l'Assistance M ecanique), which showed that among 520 mechanical circulatory support recipients implanted in France between 2000 and 2006, 73% underwent biventricular support [7]. One potential explanation is that many recipients were referred too late, once the patient was in severe cardiogenic shock with multiorgan dysfunction, thus precluding safe isolated left ventricular support.…”
Section: Commentsupporting
confidence: 89%
“…Furthermore, the TAH compares favourably with BiVAD devices in terms of early/mid-term survival or stroke. 4,17,18 This is likely because of the complete removal of both ventricles, the absence of residual thrombi and the use of shorter drivelines with large-diameter cannula. Also, local antithrombotic management could be associated with those low rates of neurologic events.…”
Section: Survival After Transplantationmentioning
confidence: 99%
“…The use of ECMO has been described in neonates, infants and adults in the setting of incessant arrhythmias leading to progressive severe cardiogenic shock (18)(19)(20)(21). VA ECMO provides vital organ perfusion and permits medical treatment in the setting of cardiogenic shock from refractory VT (22,23).…”
Section: Therapeutic Options For Vtmentioning
confidence: 99%